Analysis of Factors Affecting The Rupiah Exchange Rate Against The US Dollar - Priyojadmiko, Eko; Azizi, Muhammad (Nomico, 2024)
This study aims to identify and analyze the main factors that influence the Rupiah exchange rate against the US Dollar. The exchange rate is an important indicator that affects various sectors of the Indonesian economy, including international trade, inflation, and foreign investment. The method used is quantitative analysis with a multiple linear regression approach, using secondary data from Bank Indonesia, financial markets, and other related sources. The results of the study indicate that internal factors, such as inflation and BI interest rates, as well as external factors, such as the Fed interest rate and global commodity prices, play a significant role in determining exchange rate fluctuations. Higher inflation and an increase in the Fed interest rate tend to weaken the Rupiah, while an increase in the BI interest rate and foreign exchange reserves strengthen the Rupiah. In addition, global commodity prices also affect the stability of the Rupiah, especially through the impact on the trade balance. This study highlights the importance of appropriate monetary policy, foreign exchange market intervention, and foreign exchange reserve management in maintaining exchange rate stability. Understanding these factors is expected to help policymakers in dealing with global market dynamics and maintaining the stability of the Indonesian economy.